Essentials of teaching physical education - 3G Elearning (USA 3G E-Learning LLC, 2017)
Physical education refers to the instruction of physical activities and games. Specifically, it is used to denote the courses in school in which students receive instruction and practice in physical exercise in order to promote good health. Physical Education is "education through the physical." It aims to develop students' physical competence and knowledge of movement and safety, and their ability to use these to perform in a wide range of activities associated with the development of an active and healthy lifestyle. It also develops students' confidence and generic skills, especially those of collaboration, communication, creativity, critical thinking and aesthetic appreciation. These, together with the nurturing of positive values and attitudes in PE, provide a good foundation for students' lifelong and life-wide learning. --Back cover
Deals with enduring themes and contemporary issues in primary and secondary physical education. Helps teachers to use the teaching for learning approach to K-12 physical education.Offers a wealth of knowledge for teaching todays diverse student population. - Website
Downloadable workbook included in the DVD.
Keywords: Physical education and training; Physical education and training -- Study and teaching